A Decade of Environment Management in Chile - Ruthenberg, Ina-Marlene (World Bank, Washington, DC, 2014)
This publication presents an evaluation of the Environmental Institutions Development Project in Chile, selected by Bank management to be part of an intensive learning process in final project evaluation, given its contributing factor to the Bank's knowledge base on environmental institutional development projects. The first part of the publication focuses on the project as catalyst for culture change, and contains excerpts from lessons learned, with extensive input from the Project's implementing agency - Comision Nacional del Medio Ambiente (CONAMA) - government officials, the private sector, nongovernmental organizations, and academia. Such lessons indicate that in the absence of a national policy framework, particularly where a tradition of coordination in the subject does not yet exist, it is necessary to limit the project's objectives, but include an aggressive awareness promotion, and consensus on environmental issues, with a direct focus on human resources development in respect to environmental decision-making in sector agencies. The second part, reflects on the evolution of environmental institutional development, through working papers presented at, and compiled from the Seminar on Environmental Management, covering issues such as design, and progress in environmental management, the roles of the public, and private sectors, as well as that of civil society's perspectives. Further subjects acknowledge international influences from an industry's perspective on environmental quality, and impact, and, address how to strengthen the ties between environmental institutions, and the international community.